Variation of Laser Intensity on the Healing of Cutaneous Wounds - Do Nascimento, Patrícia M.; Pinheiro, Antonio Luiz B.; Salgado, Miguel A.C. [UNESP]; Ramalho, Luciana M. Pedreira (SPIE, the international society for optics and photonics, 2003)
Tissue repair is an integration of dynamic interactive processes that involves soluble mediators, blood components, production of extra-cellular matrix and mesenchymal cells. Many studies involving the use of LLLT shows that the healing process is favored by such therapy. The aim of this work was to evaluate, through histological analysis, the tissue effects of cutaneous wounds submitted to different intensities and a same irradiation dose with lasers in λ670 or λ685nm. Eighteen animals were divided in two experimental groups according to wavelength used (λ670 or λ685nm). Each one of these groups was divided still in three subgroups of three animals each, related to the intensity of applied irradiation (2, 15 or 25mW). Twelve animals acted as untreated controls and were not irradiated. The irradiation was carried out during seven days. The animals were sacrificed eight days after surgery. The specimens were removed, kept in 4% formaldehyde for 24 hours, routinely prepared to wax, stained with H&E and analyzed under light microscopy. The histological characteristics observed, so much in the irradiated animals, as in the control, they are indicative of a substitution repair process, however, the LLLT modulatory positive effect was observed, in the healing process, mainly associate to the use of the shorter wavelength and low power. The results of the present study indicate that LLLT improves cutaneous wound repair and best results are achieved when higher potencies associated to short wavelengths or lower potencies associated to higher wavelengths are used.
Keywords: Laser Therapy; LLLT; Tissue repair; Wound Healing; Blood; Dosimetry; Histology; Irradiation; Laser surgery; Monochromators; Optical microscopy; Tissue; Cutaneous wounds; Laser intensity; Laser tissue interaction